2016
DOI: 10.1257/mac.20120257
|View full text |Cite
|
Sign up to set email alerts
|

In the Wrong Hands: Complementarities, Resource Allocation, and TFP

Abstract: I explore mismatch between firms and their managers as a source of variation in aggregate output and total factor productivity (TFP). The model is calibrated to match observations on the size distribution of US manufacturing firms, managerial compensation, and aggregate moments in the national accounts. Quantitatively, small deviations from assortative matching can have sizeable effects on output and TFP. "Cronyism," where managerial positions are allocated by status rather than talent, imposes a substantial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Overall, the evidence presented in this section is consistent with the presence of significant di↵erences in managerial assignment frictions across countries. These findings are complementary to Alder (2016), who develops a similar idea in the context of a calibrated macro model and finds deviations from assortative matching to have large e↵ects on output and TFP across countries.…”
Section: Figure 7: Productivity Residuals Densities By Development Levelmentioning
confidence: 44%
“…Overall, the evidence presented in this section is consistent with the presence of significant di↵erences in managerial assignment frictions across countries. These findings are complementary to Alder (2016), who develops a similar idea in the context of a calibrated macro model and finds deviations from assortative matching to have large e↵ects on output and TFP across countries.…”
Section: Figure 7: Productivity Residuals Densities By Development Levelmentioning
confidence: 44%
“…Similarly, Ilmakunnas et al [20], Sharma et al [21], Baltagi et al [22] observed positive externalities of production workers and their characteristics to productivity, however Unel [23] and Alder [24] could not observed the said relationships. In the same line and with respect to ownership, the findings observed by Curcio [25] and Baltagi et al [22] contradicted each other.…”
Section: Econometric Issuesmentioning
confidence: 92%
“…In contrast to Chang et al (2010) and Taylor (2013), this study uses stock price reactions to sudden deaths to examine whether executives are paid for their contribution to shareholder value; it then uses this relationship to elicit an estimate of how rent is shared between executives and shareholders. The main advantages of our experiment are that deaths are exogenous, unlike the turnover events in Chang et al (2010), and that our method does not require the strong assumptions of a structural model, as do the models of Gabaix and Landier (2008), Terviö (2008), Alder (2012), and Taylor (2013).…”
Section: Prior Literature On Executive Compensationmentioning
confidence: 99%
“…Terviö (2008) finds that CEOs capture roughly 20% of the value they add to their firms. Alder (2012) relaxes the Gabaix and Landier (2008) assumption of a unity elasticity of substitution between firm quality and executive ability, and finds that CEOs might capture greater rent than the amount that Gabaix and Landier (2008) and Terviö (2008) suggest. In contrast, Taylor (2013) uses a structural model and finds that the surplus from learning is split equally between the executive and shareholders when news about CEO ability is good, and that the CEO completely avoids the negative surplus resulting from bad news.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation